2016
DOI: 10.3390/molecules21101285
|View full text |Cite
|
Sign up to set email alerts
|

Acacetin Protects Mice from Staphylococcus aureus Bloodstream Infection by Inhibiting the Activity of Sortase A

Abstract: Staphylococcus aureus (S. aureus) is a major cause of infection in hospitals and communities.Widespread dissemination of multi-drug resistant S. aureus is a serious threat to the health of humans and animals. An anti-virulence strategy has been widely considered as an alternative therapeutic approach. Inhibitors of virulence factors are able to treat S. aureus infections without influencing the growth or viability of bacteria and rarely lead to bacterial resistance. Sortase A (SrtA) is a membrane-associated cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 36 publications
(46 reference statements)
0
16
0
1
Order By: Relevance
“…S. aureus surface proteins include clumping factors (ClfA and ClfB), which are essential for the adhesion of S. aureus to fibrinogen (Bi et al, 2016 ). These proteins are mainly anchored by sortase A to the cell wall and play significant roles in the formation of biofilms (Cascioferro et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus surface proteins include clumping factors (ClfA and ClfB), which are essential for the adhesion of S. aureus to fibrinogen (Bi et al, 2016 ). These proteins are mainly anchored by sortase A to the cell wall and play significant roles in the formation of biofilms (Cascioferro et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory effect of kaempferol on the activity of SrtA was measured based on the fluorescence changes. The sortase A (SrtA) activity inhibition assay was conducted according to a method described previously (Bi et al, 2016 ). The experiment was performed in black 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, accumulating studies have tried to find effective xenophagy-implicated agents to target Salmonella replication ( Table 2). It is well documented that many phenolic compounds, such as Carvacrol (Gaio et al, 2017), Thymol (Marchese et al, 2016), Quercetin (Wang et al, 2018), Resveratrol (Hwang and Lim, 2015), Acacetin (Bi et al, 2016), and Epigallocatechin gallate (Nakasone et al, 2017) exhibit antibacterial activity. Recently, Al Azzaz et al (2019) found that Resveratrol promotes the autophagy-dependent elimination of intracellular Salmonella both in vitro and in vivo.…”
Section: Certain Drugs Regulate Xenophagy To Combat Salmonella Infectionmentioning
confidence: 99%
“…These results were consistent with previous studies that reported many natural products exerted inhibitory effect on the adhesion of S. aureus to brinogen. 2,23,38,39 Hence, it can be inferred that CHQA might inhibit the attachment phase of biolm formation by affecting the adhesion of S. aureus to host surface, eventually lead to weak biolm formation.…”
Section: Chqa Reduced S Aureus Adhesion To Brinogenmentioning
confidence: 99%